Occupational physical activity assessment for chronic disease prevention and management: A review of methods for both occupational health practitioners and researchers. Issue 6 (2nd June 2016) - Scott, Kenneth A.; Browning, Raymond C.
ABSTRACT: Occupational physical activity (OPA) is an occupational exposure that impacts worker health. OPA is amenable to measurement and modification through the hierarchy of controls. Occupational exposure scientists have roles in addressing inadequate physical activity, as well as excessive or harmful physical activity. Occupational health researchers can contribute to the development of novel OPA exposure assessment techniques and to epidemiologic studies examining the health impacts of physical activity at work. Occupational health practitioners stand to benefit from understanding the strengths and limitations of physical activity measurement approaches, such as accelerometers in smartphones, which are already ubiquitous in many workplaces and in some worksite health programs. This comprehensive review of the literature provides an overview of physical activity monitoring for occupational exposure scientists. This article summarizes data on the public health implications of physical activity at work, highlighting complex relationships with common chronic diseases. This article includes descriptions of several techniques that have been used to measure physical activity at work and elsewhere, focusing in detail on pedometers, accelerometers, and Global Positioning System technology. Additional subjective and objective measurement strategies are described as well.